2009
DOI: 10.1242/dev.034967
|View full text |Cite
|
Sign up to set email alerts
|

Foxg1promotes olfactory neurogenesis by antagonizingGdf11

Abstract: Foxg1, a winged-helix transcription factor, promotes the development of anterior neural structures; in mice lacking Foxg1, development of the cerebral hemispheres and olfactory epithelium (OE) is severely reduced. It has been suggested that Foxg1 acts by positively regulating the expression of growth factors, such as Fgf8, which support neurogenesis. However, Foxg1 also binds Smad transcriptional complexes, allowing it to negatively regulate the effects of TGFβ family ligands. Here, we provide evidence that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 58 publications
5
88
0
Order By: Relevance
“…Accordingly, inhibition of Bmp activity resulted in a decrease of pSmad1/5/8, which promoted the generation of sensory epithelial cells at the expense of respiratory epithelial cells. In line with our findings, recent results have suggested that Fgf-induced Foxg1 (Storm et al, 2006) promotes the generation of olfactory sensory neurons via upregulation of the Tgfb antagonist follistatin, which antagonizes Gdf11 activity in the olfactory pit (Kawauchi et al, 2009). In summary, we find that at olfactory placodal and pit stages, Fgf and Bmp signals act in an opposing manner to regulate sensory versus respiratory epithelial cell fate decision.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, inhibition of Bmp activity resulted in a decrease of pSmad1/5/8, which promoted the generation of sensory epithelial cells at the expense of respiratory epithelial cells. In line with our findings, recent results have suggested that Fgf-induced Foxg1 (Storm et al, 2006) promotes the generation of olfactory sensory neurons via upregulation of the Tgfb antagonist follistatin, which antagonizes Gdf11 activity in the olfactory pit (Kawauchi et al, 2009). In summary, we find that at olfactory placodal and pit stages, Fgf and Bmp signals act in an opposing manner to regulate sensory versus respiratory epithelial cell fate decision.…”
Section: Discussionsupporting
confidence: 93%
“…After transfection and collection of (GFP+)-transfected using a FACScan flow cytometer, total RNAs were extracted, converted to cDNA, and CDKN1A expression was studied by real-time RT-PCR. As reported in previous reports [Seoane et al 2004;Kawauchi et al 2009;Chan et al 2009], we first observed that overexpression of the wild-type protein FOXG1 in cells results in a decrease (~40%) of CDKN1A expression as compared with untransfected cells (data not shown). Secondly, we showed that overexpression of the p.R244C mutant results in an increase (Fig.…”
Section: The Pr244c Mutation Affects the Cdkn1a Expressionsupporting
confidence: 82%
“…Target genes include cell cycle inhibitors, such as the cyclin-dependent kinase inhibitor 1A (p21, Cip1) (CDKN1A) gene [Seoane et al 2004;Kawauchi et al 2009;Chan et al 2009]. FoxG1 is known to be a potent inhibitor of the transforming growth factor (TGF) β-regulated signalling by inhibiting the TGFβ-dependent transcription of the CDKN1A gene, encoding a cell cycle protein that may induce cell cycle exit in neural precursors [Siegenthaler and Miller, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…The relative levels of expression of the transcription factors ASCL1 and SOX2 appears to underlie cell fate bias, with cells that maintain SOX2 expression committing to a glial fate (Gokoffski et al, 2011;Krolewski et al, 2012). Several secreted factors have been identified so far as regulators of cell fate choice in the OE, including activins, BMPs, GDF11 and follistatin (Gokoffski et al, 2011;Kawauchi et al, 2009;Shou et al, 2000;Wu et al, 2003). In addition to these proteins, members of the Notch family of receptors and their transmembrane ligands of the Delta family are expressed in the OE and have been proposed to regulate the development and maintenance of OE cell populations (Carson et al, 2006;Cau et al, 2000;Schwarting et al, 2007).…”
Section: Cell-cell Interactions In Oe Developmentmentioning
confidence: 99%
“…While several members of the TGFβ family of molecules have been implicated in the generation and survival of ORNs, much less is known about the signals that regulate the production of SUS cells (Gokoffski et al, 2011;Kawauchi et al, 2009Kawauchi et al, , 2005Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%